Reference in Lyric "Beautiful Girl" by Jose Marichan: Pragmatics Study - Ardian Maha Putra; Heri Heryono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The subject of this study is a reference found in Jose Marichan's song "Beautiful girl." The study's goals are to identify the function of reference, find the different types of referencing expressions in the lyrics and to explain how they are used. This study is based on descriptive data. Jose Marichan's song "Beautiful girl" was used as a data source for this study. The researcher discovered pronouns, proper names, definite noun phrase and indefinite noun phrase while collecting information. The researcher next analyzes the data and explains why it is classified as satisfying referring expression. According to the findings indefinite noun phrase with two data (13%), pronoun with twelve data (80%), and definite noun phrase with one data (7%), the function of reference is to allow the listener or reader to identify something, while referring expression is to identify the types.